Separated : inside an American tragedy - Soboroff, Jacob (Custom House, 2020)
"A deeply reported, newsbreaking account the humanitarian crisis of our time by the journalist who has been at the center of the story: MSNBC correspondent Jacob Soboroff, winner of the 2019 Walter Cronkite Award, offers a chilling expose of the human cost of the Trump administration's border and immigration policies"--